The administrative service system of patient reception at regional public hospital - Deby Rara Yolanda; Sitti Raodhah; Hasbi Ibrahim (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2020)
In Indonesia, the most commonly used health insurance is the service issued by Badan Penyelenggara Jaminan Social or BPJS (Social Security Administration) that collaborates with many hospitals such as H. AndiDaengRddja Regional Public Hospital in Bulukumba Regency. The purpose of this study was to determine the administrative service system implemented by the hospital in accepting BPJS patients in the emergency room. This research uses qualitative approach with a case study as the research design. The research data are obtained through in-depth interviews. In addition to that, this research collects its research data through field observations and a review of related previous studies. The findings reveal that the hospital management applies the following strategies in the division of administrative services: (1) planning through trainings and workshops provided for the human resources as well as the formulation of RUK and RPK; (2) organising through trainings involving a number of institutions within Regional Public Hospital; (3) actuating through an execution of administrative services for BPJS users; (4) controlling through supervision facilitated by the hospital management; (5) evaluating that addresses the process of human resources quality promotion through databased information trainings. In conclusion, the findings of this research are hoped to provide insights that can be useful for the hospital management specifically the emergency unit to improve their performance in providing services for BPJS users. They can start by assessing the development and training, program execution and evaluation aspects as well as by improving the facilities and infrastructure.